Synthesis of metal oxides/sulfides-based nanocomposites and their environmental applications: a review. (December 2022) - Dharmalingam, Poobana; Palani, Geetha; Apsari, Retna; Kannan, Karthik; Lakkaboyana, Sivarama Krishna; Venkateswarlu, Katta; Kumar, Vinay; Ali, Yuzir
Abstract: The development of new/novel methods has attained a large potential in materials science as a dependable, sustainable, and environment friendly processes in making a huge number of nanomaterials/nanoparticles including metal/metal oxide nanomaterials, nanocomposites as well as bio-inspired chemical compositions. In this connection, the synthesis of these nanomaterials is the crucial part, and several significant protocols including green processes have appeared in the literature which can be easily exercised in research laboratories and industries. This article outlines the essential procedures for the synthesis of metal oxide/sulfide-based nanocomposites. Then, the environmental application of these metal oxide/sulfide nanocomposites in the photocatalytic removal of organic dye molecules has been reviewed. These metal oxide/sulfide-based nanocomposites are found to be fundamental and indispensable substances in these applications, and they have enormous scope for the future research. Hence, this article with the selected sustainable area of research may be highly useful to the scientific community toward designing and applying these materials. Further, this article also discloses the fundamental properties of metal oxide/sulfide-based nanocomposites in energy storage, antimicrobial and heavy metal ion-sensing applications of metal oxide/sulfide nanocomposites. Graphical abstract: Image 1 Highlights: Preparation methods of metal oxide/sulfide based nanocomposites. Organic dye removal applications of metal oxide/sulfide nanocomposites. Photocatalytic activities of metal oxide/nanocomposites. Antibacterial and heavy metal sensing activities of metal oxide/sulfide nanocomposites. Useful to the scientific community working on metal oxide/sulfide nanocomposites.